2004
DOI: 10.1177/000348940411300710
|View full text |Cite
|
Sign up to set email alerts
|

Use of a “Hands-Free” Tracheostoma Valve in Patients with Laryngectomy and Tracheoesophageal Puncture

Abstract: The goals of the study were 1) to investigate the relationship between tracheal air pressure and the tracheostoma valve seal in patients with laryngectomy and tracheoesophageal puncture (TEP) and 2) to assess whether tracheal pressure contributes to the duration of the valve seal. Ten patients with TEP after laryngectomy underwent training with an outer Blom-Singer tracheostoma valve and a 30-day trial with this "hands-free" speaking valve. We found that tracheal pressure was not a significant predictor variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The participants who had previous experience with the use of an ASV managed to achieve a significantly longer airtight seal (with or without ENB) of the adhesive baseplate compared to patients who had not used a hands‐free valve before (Table III). This finding is in keeping with Roxburgh and Perry 14…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The participants who had previous experience with the use of an ASV managed to achieve a significantly longer airtight seal (with or without ENB) of the adhesive baseplate compared to patients who had not used a hands‐free valve before (Table III). This finding is in keeping with Roxburgh and Perry 14…”
Section: Discussionsupporting
confidence: 91%
“…Roxburgh and Perry14 assessed the relation between tracheal pressures during TOP speech and adhesive loosening in a 30‐day trial with a Blom–Singer adjustable tracheostoma valve (ATV) (Inhealth Technologies, Carpinteria, CA). Their group found that tracheal pressure was not a significant predictor variable in the lifetime of an adhesive seal.…”
Section: Discussionmentioning
confidence: 99%
“…1 Benefits of tracheoesophageal puncture over other alaryngeal speech methods include longer phonation time, more syllables per breath and greater maximum intensity level. 2 More contentious, however, is the timing of the tracheoesophageal puncture. The original description of tracheoesophageal puncture insertion was as a secondary procedure in patients post-laryngectomy, but increasingly it has been performed primarily as part of the laryngectomy.…”
Section: Introductionmentioning
confidence: 99%
“…During manual occlusion, counter‐pressure is applied to balance the tracheal back pressure needed for tracheo–esophageal speech. However, one study indicated that tracheal back pressure was not a significant factor to predict valve seal attachment time of the Blom‐Singer TSV 10…”
Section: Introductionmentioning
confidence: 99%
“…However, one study indicated that tracheal back pressure was not a significant factor to predict valve seal attachment time of the Blom-Singer TSV. 10 Other disadvantages of the current fixation methods are painful skin irritation or even skin or soft tissue infection caused by skin maceration and traction, time-consuming cleaning and reattaching, noise, dislodgement, and high financial cost.…”
Section: Introductionmentioning
confidence: 99%